Auditory hair cell defects as potential cause for sensorineural deafness in Wolf-Hirschhorn syndrome - Mohi Ahmed; Kiyoe Ura; Andrea Streit (The Company of Biologists, 2015)
WHSC1 is a histone methyltransferase (HMT) that catalyses the addition of methyl groups to lysine 36 on histone 3. In humans, WHSC1 haploinsufficiency is associated with all known cases of Wolf-Hirschhorn syndrome (WHS). The cardinal feature of WHS is a craniofacial dysmorphism, which is accompanied by sensorineural hearing loss in 15% of individuals with WHS. Here, we show that WHSC1-deficient mice display craniofacial defects that overlap with WHS, including cochlea anomalies. Although auditory hair cells are specified normally, their stereocilia hair bundles required for sound perception fail to develop the appropriate morphology. Furthermore, the orientation and cellular organisation of cochlear hair cells and their innervation are defective. These findings identify, for the first time, the likely cause of sensorineural hearing loss in individuals with WHS.